2018
DOI: 10.3390/molecules23112759
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants Used for the Traditional Management of Diabetes in the Eastern Cape, South Africa: Pharmacology and Toxicology

Abstract: The use of medicinal plants for the management of diabetes mellitus is on the rise in the developing countries, including South Africa. There is increasing scientific evidence that supports the claims by the traditional healers. In this review, we compare the families of previously reported anti-diabetic plants in the Eastern Cape by rating the anti-diabetic activity, mode of action and also highlight their therapeutic potentials based on the available evidence on their pharmacology and toxicity. Forty-five pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 90 publications
(112 reference statements)
0
40
0
1
Order By: Relevance
“…These plants are used as ATM by communities for conditions, mainly diabetes mellitus, hypertension, HIV infection and others. They also form part of the list of potent medicinal plants and those with potential to be developed into commercial products [59][60][61][62][63][64].…”
Section: Research In African Traditional Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…These plants are used as ATM by communities for conditions, mainly diabetes mellitus, hypertension, HIV infection and others. They also form part of the list of potent medicinal plants and those with potential to be developed into commercial products [59][60][61][62][63][64].…”
Section: Research In African Traditional Medicinementioning
confidence: 99%
“…As an example, some of the plants used for diabetes mellitus, such as Aloe ferox, have also been investigated scientifically for anti-diabetic properties. The leaf, as well as the sap from the leaf, of Aloe ferox is commonly used in ATM, and in vitro and in vivo studies have shown that it has insulin-increasing activity which may be the mechanism by which it reverses hyperglycaemia [59,62,97,98]. Ubulawu, a traditional medicine prepared from roots of Silene bellidioides and stem of Helinus integrifolius, is used to cleanse the body and the mind.…”
Section: Overview Of African Traditional Medicine Practicementioning
confidence: 99%
“…10 In traditional medicine, medicinal plants are used for the treatment of diabetes; these plants are a rich source of hypolipidemic, hypoglycemic, and antioxidant agents, such as phenols, flavonoids, gallotannins, and other related polyphenols. 11,12 Wheatgrass (T. aestivum germinated over a period of 6-10 days) was found to improve metabolic and lipid profiles 13 and to restore the levels of plasma glucose, insulin, and liver glycogen. 14,15 The nutrient value of germinated grains depends on the conditions in which they are grown.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the increase in the prevalence of diabetes in the population has been increasing, therefore, the use of medicinal plants has stood out in this area, with a large investment in studies for the characterization of chemical substances derived from plant species in order to investigate the mechanisms of action of these compounds in comparison with synthetic drugs (Odeyemi & Bradley, 2018).…”
Section: Resultsmentioning
confidence: 99%